2022
DOI: 10.1093/cercor/bhac002
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of the timing and intensity of a stimulus propagate to the auditory periphery through the medial olivocochlear reflex

Abstract: Expectations concerning the timing of a stimulus enhance attention at the time at which the event occurs, which confers significant sensory and behavioral benefits. Herein, we show that temporal expectations modulate even the sensory transduction in the auditory periphery via the descending pathway. We measured the medial olivocochlear reflex (MOCR), a sound-activated efferent feedback that controls outer hair cell motility and optimizes the dynamic range of the sensory system. MOCR was noninvasively assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Given that wave ii and iii represent neural activity in the cochlear nucleus and superior olivary complex, respectively [14], this finding strongly supports the hypothesis that auditory probability encoding at population level is happening already below the inferior colliculus, as it has been suggested in former studies [8,15]. In fact, effects of novelty detection have recently been described for an even lower auditory structure, the cochlea [16,17]. In these reports, the authors propose that the medial olivocochlear reflex is responsible for those effects by suppressing outer hair cell activity, mediated by feedback from the cortex.…”
Section: Abrssupporting
confidence: 83%
“…Given that wave ii and iii represent neural activity in the cochlear nucleus and superior olivary complex, respectively [14], this finding strongly supports the hypothesis that auditory probability encoding at population level is happening already below the inferior colliculus, as it has been suggested in former studies [8,15]. In fact, effects of novelty detection have recently been described for an even lower auditory structure, the cochlea [16,17]. In these reports, the authors propose that the medial olivocochlear reflex is responsible for those effects by suppressing outer hair cell activity, mediated by feedback from the cortex.…”
Section: Abrssupporting
confidence: 83%
“…Learned expectations about stimulus properties influenced the intensity of the MOC reflex. This finding provides a small glimpse of the complexity of functions and tasks that MOC-mediated modulation could be involved in (Otsuka et al, 2022). Overall, the MOC efferent fibres seem to represent a common final route of a number of pathways that assert descending control on the inner ear.…”
mentioning
confidence: 78%
“…In a recent paper, Otsuka et al. (2022) showed that the intensity of the MOC reflex can be controlled by goal‐oriented behaviour. Learned expectations about stimulus properties influenced the intensity of the MOC reflex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Slow-rate cortical oscillations synchronize with regularly presented stimuli [7], and their phases are aligned as a function of the temporal predictability of a sensory event [8]. We recently reported that the medial olivocochlear reflex (MOCR) is modulated by the presentation of visual cues that anticipate the arrival of a stimulus sound [9], suggesting that the most peripheral stage of the hearing system, the cochlea, can be modulated by temporal predictability.…”
Section: Introductionmentioning
confidence: 99%